2012
DOI: 10.7150/jca.4107
|View full text |Cite
|
Sign up to set email alerts
|

Additively Enhanced Antiproliferative Effect of Interferon Combined with Proanthocyanidin on Bladder Cancer Cells

Abstract: Although interferon (IFN) has been often used as immunotherapy for bladder cancer, its efficacy is rather unsatisfactory, demanding further improvement. Combination therapy is one of viable options, and grape seed proanthocyanidin (GSP) could be such an agent to be used with IFN because it has been shown to have anticancer activity. We thus investigated whether combination of IFN and GSP might enhance the overall antiproliferative effect on bladder cancer cells in vitro. Human bladder cancer T24 cells were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…For instance, the synergic cell growth inhibition and apoptosis of IFN-α are observed in human T-cell lymphotropic virus type I-transformed cells combined with arsenic trioxide (8), in transformed T-and monocytoid cell lines combined with IL-21 (9), in HCC combined with 5-fluorouracil (10), or in bladder cancer cells combined with proanthocyanidin (11). These results indicate that a combinatorial strategy is more effective to antitumor action.…”
Section: Introductionmentioning
confidence: 67%
“…For instance, the synergic cell growth inhibition and apoptosis of IFN-α are observed in human T-cell lymphotropic virus type I-transformed cells combined with arsenic trioxide (8), in transformed T-and monocytoid cell lines combined with IL-21 (9), in HCC combined with 5-fluorouracil (10), or in bladder cancer cells combined with proanthocyanidin (11). These results indicate that a combinatorial strategy is more effective to antitumor action.…”
Section: Introductionmentioning
confidence: 67%
“…Interestingly, PAs were also applied as chemosensitive candidates to combine with chemotherapeutic agents for synergistic anticancer efficacy, such as interferon, doxorubicin, cisplatin, and so on . In a previous study, the combination of interferon‐α2b (50K IU/mL) and GSP (25 μg/mL) showed a drastic growth reduction up to 95% via induction of cell cycle arrest in G1 . With the isolation of PAs from Urceola huaitingii , nine novel compounds were identified and the anticancer efficacies of them were also investigated, which showed that PAs with high degrees of polymerization might have higher antiproliferative effect and PAs with two doubly interflavonoid linkages possessed stronger synergistic anticancer efficacy with chemotherapeutic agents (doxorubicin or cispaltin) compared to those with single doubly interflavonoid linkage .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…Interestingly, PAs were also applied as chemosensitive candidates to combine with chemotherapeutic agents for synergistic anticancer efficacy, such as interferon, doxorubicin, cisplatin, and so on . In a previous study, the combination of interferon‐α2b (50K IU/mL) and GSP (25 μg/mL) showed a drastic growth reduction up to 95% via induction of cell cycle arrest in G1 .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…One of the strategies would be to investigate hesperidin or hesperetin as coadjuvant of the chemotherapeutics regiment in bladder cancer (e.g., DOX, CIS, MMC, etc.). Perspectives of this research might be great, if we joint our expertise in bladder cancer on animals [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] and easiness of obtaining hesperidin and hesperetin in our laboratories. At last bit not at least, this mini-review shows the importance of introducing new, nontoxic and economically feasible natural products for the cancer treatment.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%